Event-related potentials reflect spectral differences in speech and non-speech stimuli in children and adults - Èeponienë, R. (2008)
OBJECTIVE: Event-related brain potentials (ERP) may provide tools for examining normal and abnormal language development. To clarify functional significance of auditory ERPs, we examined ERP indices of spectral differences in speech and non-speech sounds. METHODS: Three Spectral Items (BA, DA, GA) were presented as three Stimulus Types: syllables, non-phonetics, and consonant-vowel transitions. Fourteen 7–10-year-old children and 14 adults were presented with equiprobable Spectral Item sequences blocked by Stimulus Type. RESULTS: Spectral Item effect appeared as P1, P2, N2, and N4 amplitude variations. The P2 was sensitive to all Stimulus Types in both groups. In adults, the P1 was also sensitive to transitions while the N4 was sensitive to syllables. In children, only the 50-ms CVT stimuli elicited N2 and N4 spectral effects. Non-phonetic stimuli elicited larger N1-P2 amplitudes while speech stimuli elicited larger N2- N4 amplitudes. CONCLUSIONS: Auditory feature processing is reflected by P1-P2 and N2-N4 peaks and matures earlier than supra-sensory integrative mechanisms, reflected by N1-P2 peaks. Auditory P2 appears to pertain to both processing types. SIGNIFICANCE: These results delineate an orderly processing organization whereby direct feature mapping occurs earlier in processing and, in part, serves sound detection whereas relational mapping occurs later in processing and serves sound identification.